Analisis Kelayakan Finansial Usaha Penyulingan Minyak Nilam di Desa Garuda Kecamatan Padangguni Kabupaten Konawe - Aliqadri Aliqadri; Rayuddin Rayuddin; Bambang Indro Yuwono (Agrisurya, 2022)
Patchouli oil refining business in Garuda Village, Padangguni District, Konawe Regency is under the responsibility of the Village Owned Enterprise (BUMDES). The purpose of this research is to see the income and financial feasibility of the patchouli oil refining business carried out in Garuda Village, Padangguni District, Konawe Regency. The research method is a case study approach to the management unit of the Patchouli oil refining business belonging to BUMDES. Descriptive quantitative data analysis to answer the problems of income and financial feasibility of patchouli oil refining business. The results of this study indicate that the net income or profit value of patchouli oil refining business is Rp. 26,634,867 per year. Meanwhile, the results of the financial analysis show that BEP revenues are greater than real revenues with a "payback period" of six years and three months in return for investment in the patchouli oil refining business.